Cardiac Troponin T and Illness Severity in the Very-Low-Birth-Weight Infant - Danielle N. Lopes; José M. Moraes Ramos; Maria Elizabeth Lopes Moreira; Jofre A. Cabral; Manoel de Carvalho; José Maria de Andrade Lopes (International Journal of Pediatrics)
Introduction. Respiratory distress are very common in Very-low-birth-weight (VLBW) infants and Myocardial injury may play a role in the disease outcome. Cardiac troponin T (cTnT) is the most useful marker of injury in adult population, but has not been extensively studied in this population. Aim. To study the role of cTnT in VLBW infants and its association with clinical outcomes. Methods. All VLBW infants admitted to our NICU were included in the study. Echocardiography and blood samples for cTnT determination were collected at 24 and 48 hours of life, and values >0.1 ng/mL were considered CTnT-positive values. Results. A total of 116 neonates had their blood samples collected. The median cTnT concentration within 24 hours was 0.191 (0.1–0.79) ng/mL and within 48 hours was 0.293 (0.1–1.0) ng/mL. A logistic regression analysis showed that PDA, low GA, and use of dopamine were independently associated with positive cTnT and abnormal Dopplerfluxometry and diuretics use had protective effects and was independently associated with troponin values. Conclusion. We observed a high prevalence of positivecTnT values in VLBW infants associated with illness severity. Our findings suggest that cTnT may be a useful and early marker of myocardial injury in VLBW infants.